A study of management of steel parts leftover generated by the maintenance of heavy vehicles - Buono, Pedro Henrique de Oliveira; Dias, Karina Tonelli Silveira; Braga Junior, Sergio Silva; Satolo, Eduardo Guilherme (Revista de Negócios, 2016)
The objective of this study was to analyze the waste management in a maintenance workshop for heavy vehicles. To achieve this, purpose a study in the state of São Paulo - Brazil was conducted in a maintenance workshop for heavy vehicles providing services for the major plants of this sector in the region. Data were collected over a period of 18 months, using the Wuppertal method to measure the environmental gains. It was observed that more than 245 tons of abiotic materials are no longer generated by the practice of reuse in the steel production chain. Moreover, 2,000 tons of water and 20 tons of air no longer were used to process the same steel amount that is sent for reuse in the production chain.